Rethinking Concurrent Creditor Protection in Suspension of Debt Payment Obligations - Rijal Ibnu Sani; Suartini Suartini; Ahmad Ahmad; Tri Cahya Indra Permana; Misno Misno (Universitas Muhammadiyah Tangerang, 2024)
The current practice of Suspension of Debt Payment Obligations (PKPU) in Indonesia reveals a distributive justice anomaly that disadvantages petitioning creditors. A â€œfree-riderâ€ phenomenon has emerged, whereby passive creditors obtain equal or even more favorable treatment without bearing litigation costs or the substantial legal risks associated with initiating proceedings. This inequity is exacerbated by settlement schemes that tend to marginalize initiating creditors through excessive postponement of payment schedules. This study aims to deconstruct the application of the Pari Passu Pro Rata Parte principle when applied without regard to litigation cost contributions, and to formulate a more equitable framework of legal protection for petitioning creditors as initiators of the restructuring process. The research employs a normative juridical method, utilizing conceptual and statutory approaches to evaluate the consistency between bankruptcy procedures and the values of distributive justice. The findings indicate that the absence of a litigation cost recovery mechanism generates structural injustice within the PKPU framework. From a legal standpoint, the petitionerâ€™s financial burden and procedural initiative should be recognized as prioritized costs within the settlement plan. In conclusion, the PKPU regime requires policy redefinition to ensure financial protection for petitioning creditors, prevent exploitation by passive creditors, and preserve the integrity of commercial law enforcement.